2020
DOI: 10.1007/s13555-020-00412-9
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab Therapy for Recalcitrant Eosinophilic Annular Erythema in an Adult: A Case Report and Review of Treatment Options

Abstract: Eosinophilic annular erythema (EAE) is a rare condition with a chronic relapsing and remitting course, characterized by the presence of annular or polycyclic erythematous and plaque lesions and prominent tissue eosinophilia on histopathology. There is an ongoing discussion on whether EAE is a subset of Wells syndrome (eosinophilic cellulitis) or a separate entity. To date, few cases of EAE have been reported in the literature; of these, about 40 cases were in adults and fewer than ten cases were in children. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…3 Other therapies include dapsone, narrow-band UV B therapy, nicotinamide, indomethacin, cyclosporine, methotrexate, mycophenolate mofetil, mepolizumab, dupilumab, and suplatast tosilate. 3,10 Our patient had complete resolution of rash and decreased eosinophilia count after initiation of 12.5 mg of methotrexate weekly and 5 mg of prednisone daily for 1 month. To date, the rash has not recurred.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…3 Other therapies include dapsone, narrow-band UV B therapy, nicotinamide, indomethacin, cyclosporine, methotrexate, mycophenolate mofetil, mepolizumab, dupilumab, and suplatast tosilate. 3,10 Our patient had complete resolution of rash and decreased eosinophilia count after initiation of 12.5 mg of methotrexate weekly and 5 mg of prednisone daily for 1 month. To date, the rash has not recurred.…”
Section: Discussionmentioning
confidence: 77%
“…Entities that have been reported in patients with a diagnosis of EAE include autoimmune thyroid disease, autoimmune hepatitis, autoimmune pancreatitis, chronic borreliosis, renal cell carcinoma, prostate carcinoma, chronic gastritis with Helicobacter pylori infection, diabetes mellitus, chronic hepatitis C infection, chronic kidney disease, eosinophilic granulomatosis with polyangiitis, and asthma. 3 , 10 , 11 , 12 , 13 Interestingly, El-Khalawany et al 3 observed that periods of proper management of associated systemic diseases were associated with lower relapse rates and prolonged remission periods of EAE. No etiologic association between any of these disorders and EAE has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who show refractory EAE need to take OCS, hydroxychloroquine, dapsone, doxycycline, or methotrexate to control their symptoms [ 10 ]. To prevent the side effects of these drugs, innovative treatment strategies are required.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the side effects of these drugs, innovative treatment strategies are required. Mepolizumab, anti-IL-5 antibody, has been reported to be successful in treating EAE refractory to OCS administration [ 10 ]. Benralizumab is an anti-IL-5 receptor-α monoclonal antibody with antibody-dependent cell-mediated cytotoxicity that directly and rapidly eliminates eosinophils in circulating blood and tissues [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Topische und systemische Glukokortikoide und Antimalariamittel (Chloroquin oder Hydroxychloroquin), welche die Chemotaxis von Eosinophilen inhibieren, wurden mit unterschiedlichem Erfolg eingesetzt [ 1 , 2 , 4 , 7 ]. In therapierefraktären Einzelfällen wurden Erfolge mit Mepolizumab, ein humanisierter monoklonaler Antikörper gegen Interleukin 5 [ 11 ], und Dupilumab, ein Interleukin-4-Rezeptor-α-Antagonist [ 3 ], erzielt. Aufgrund des selbstlimitierenden Erkrankungsverlaufes und der zumeist milden Symptomatik muss im Einzelfall entschieden werden, ob ein Therapieversuch indiziert ist.…”
Section: Diskussionunclassified